Prevention of Mother-to-Child Transmission of HIV in Option B+ Era: Uptake and Adherence During Pregnancy in Western Uganda - Schnack, Alexandra; Rubaihayo, John; Busingye, Priscilla; Tumwesigye,Nazarius Mbona; Theuring, Stefanie (AIDS patient care and STDs, 2016)
Since 2012, lifelong antiretroviral therapy for all HIV-positive pregnant women (“Option B+”) is recommended by WHO for the prevention of mother-to-child transmission of HIV (PMTCT). Many sub-Saharan African countries have since introduced this regimen, but to date, longer-term outcome evaluations are scarce. We conducted an observational study in Fort Portal Municipality, Uganda, to describe uptake and adherence of Option B+ during pregnancy. HIV-positive women approaching antenatal care (ANC) services in two hospitals were enrolled and followed-up at monthly routine ANC visits until delivery. At each visit, next to sociodemographic and clinical data, we assessed drug adherence through pill counts. In total, 124 HIV-positive pregnant women were enrolled in our study; from these, 80.8% had not been aware of their positive serostatus before. Forty-five PMTCT clients (36.3%) never returned to ANC after their first visit. Protective factors (p < 0.05) for immediate loss to care included previous HIV status knowledge, status disclosure before or at first ANC visit, and tertiary education. Among those clients starting Option B+, the median adherence during pregnancy was 95.7% pill intake. Rather low adherence (<80%) was observed in 21.1% of clients, while more than half achieved an adherence level of ≥95%, with 40.8% of all clients being 100% adherent. The cohort's median adherence remained stable throughout the course of pregnancy. Healthcare providers should place high emphasis on individual PMTCT counseling at first ANC encounter, and pay special attention to those women previously unaware of their HIV status. However, after initial uptake, high adherence seems to be feasible for Option B+.